MENELISIK KODIFIKASI HADIS: Upaya Menakar Validitas Hadis Sebagai Sumber Kedua di Tengah Kepungan Kelompok Inkar al-Sunnah - Ulum, Bahrul (MAQASHID, 2020)
The scholars agree that hadith is a source of law, even though they differ in their opinion on the validity of a hadith. The hadith of the Prophet, which is often referred to as al-Sunnah al-Nabawiyyah, is one of the two basic resouces of the Islamic syari'at after the Qur'an. They position the hadith as a guide in carrying out activities in this world, both with regard to aspects of worship such as mu'amalah and morals. Hadith in the form of words, deeds and provisions (taqririyah), in detail, has outlined a manhaj for the life of Muslims, both individually, in families, communities and countries. The position of the hadith in Islamic syari'at is very strategic. Of course, there is no need to doubt, because the function of hadith apart from being the most urgent is interpreting the Qur'an. More than that, the function of the hadith which is no less important is as a basis in determining other laws that are not contained in the al-Qur ?an. In the past, the Companions used to listen to the Prophet's words and witness the Prophet's actions and life firsthand. In many cases, if they disagree in interpreting the verses of the Qur'an or find it difficult to determine a law, they do not hesitate to refer to the hadith of the Prophet. Of course they are very upholding the sunnah that the Prophet recently passed on as a translater of revelation that was sent to all mankind.